2022
DOI: 10.1021/acs.jpcc.1c10347
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Organic–Inorganic Hybrid Materials with Reversible Thermochromic Property and Dielectric Switching

Abstract: Among the stimuli-responsive materials, thermochromic materials have received tremendous scientific attention. However, traditional organic or inorganic thermochromic materials need a complex preparation process and possess a single performance. Herein, we report a new 1D organic−inorganic hybrid material, lead iodide hybrid, [PbI 4 •4-MAPY] (CP-1) (4-MAPY = pyridin-4-ylmethanamine), with line-sharing PbI 6 octahedral chains and excellent reversible thermochromic properties (transition between lemon yellow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Therefore, low-dimensional hybrid metal halides provide opportunities for the rapid development of high-performance thermochromism and the in-depth study of structure-property relationships. [19][20][21] In 2022, the Fu group carried out research on a lead iodide hybrid [PbI 4 -MAPY] 22 having a reversible thermochromic transition between tartrazine and carmine red; the forbidden bandwidth of the [PbI 4 ] 2À chain is narrowed from 2.72 to 2.33 eV in response to heat. It has been reported that the thermochromic behavior of hybrid structures is usually caused by lattice distortion, lattice expansion, or ion rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low-dimensional hybrid metal halides provide opportunities for the rapid development of high-performance thermochromism and the in-depth study of structure-property relationships. [19][20][21] In 2022, the Fu group carried out research on a lead iodide hybrid [PbI 4 -MAPY] 22 having a reversible thermochromic transition between tartrazine and carmine red; the forbidden bandwidth of the [PbI 4 ] 2À chain is narrowed from 2.72 to 2.33 eV in response to heat. It has been reported that the thermochromic behavior of hybrid structures is usually caused by lattice distortion, lattice expansion, or ion rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…12,[24][25][26][27][28] As a typical representative of phase transition materials, organic-inorganic hybrid compounds can form different crystal structures with various physical properties, because of the flexibility of their structural composition. [29][30][31][32][33][34][35][36] In particular, two-dimensional organic-inorganic hybrid perovskite materials have received much attention in recent years. [37][38][39][40][41][42][43][44][45][46] By tuning their molecular structures, [47][48][49][50][51][52][53] phase transition materials could exhibit an appropriate phase transition temperature and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical representative of phase transition materials, organic–inorganic hybrid compounds can form different crystal structures with various physical properties, because of the flexibility of their structural composition. 29–36 In particular, two-dimensional organic–inorganic hybrid perovskite materials have received much attention in recent years. 37–46…”
Section: Introductionmentioning
confidence: 99%
“…As one of the representatives, hybrid organic-inorganic perovskite (HOIP) [5] and derivatives (such as ABX 3 (A = monovalent organic cation (A + ), B = divalent transition metals (M 2 + ), X = halogen ion (Cl, Br, I)) exhibit good chemical structure stability and excellent properties (such as, photovoltaic/electric, [6] light detection [7] and photoluminescence (PL), [8] etc). Thus, this kind material has been widely used in photovoltaic, [9] sensors, [10] light-emitting diodes (LEDs) [11] field.…”
Section: Introductionmentioning
confidence: 99%